2007
DOI: 10.1134/s0001433807010057
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the impact of the planetary scale on the decay of blocking and the use of phase diagrams and enstrophy as a diagnostic

Abstract: -It was shown that abrupt changes in the large-scale structure of atmospheric flows may lead to the rapid decay of blocking. Analysis of phase diagrams made it possible to identify when sharp changes occurred in the dynamics of the system. The connection of these changes to the decay of blocking was estimated for three blocking events in the Southern Hemisphere. In addition to phase diagrams, enstrophy was used as a diagnostic tool for the analysis of blocking events. From the results of this analysis, four sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
63
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(69 citation statements)
references
References 41 publications
6
63
0
Order By: Relevance
“…Also, the study by [18] describes blocking as a quasistationary atmospheric state with quasi-barotropic structure, and in a quasi-barotropic flow the sum of the positive Lyapunov exponents is related to IRE. A Lyapunov exponent is the measure of the divergence or convergence of system trajectories that are initially close, and can be approximated by integrating enstrophy over a finite region known as IRE, which is vorticity squared [10,29]. The work of [29] used this technique to determine the stability or predictability within a planetry flow regime.…”
Section: Methodsmentioning
confidence: 99%
“…Also, the study by [18] describes blocking as a quasistationary atmospheric state with quasi-barotropic structure, and in a quasi-barotropic flow the sum of the positive Lyapunov exponents is related to IRE. A Lyapunov exponent is the measure of the divergence or convergence of system trajectories that are initially close, and can be approximated by integrating enstrophy over a finite region known as IRE, which is vorticity squared [10,29]. The work of [29] used this technique to determine the stability or predictability within a planetry flow regime.…”
Section: Methodsmentioning
confidence: 99%
“…IRE conjectures that the blocking domain sum of the flow enstrophy is related to the sum of the positive eigenvalues of the linearization operator of the barotropic voricity equation [2,3]. As such, IRE can also be regarded as a flow stability indicator [2,3]. The work of [2] demonstrated for three case studies of Southern Hemisphere blocking, that IRE increased locally with the decay of each blocking event, and was relatively low during the maintenance period.…”
Section: Introductionmentioning
confidence: 99%
“…The study of [1] derived a quantity called Integrated Regional Enstrophy (IRE) which can be used as a measure for change in the zonal flow that may indicate blocking. IRE conjectures that the blocking domain sum of the flow enstrophy is related to the sum of the positive eigenvalues of the linearization operator of the barotropic voricity equation [2,3]. As such, IRE can also be regarded as a flow stability indicator [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This event was noteworthy as it survived a large-scale flow regime change during early 4-7 February 2014, as the Pacific North American (PNA) teleconnection pattern changed from a positive to negative configuration during early February 2014. Earlier work (e.g., [28,29]) suggested that blocking events should not survive a transition in the large-scale flow regime, but [27] showed that, under certain conditions, these events could survive the transition. Additionally, this event is noteworthy for its longevity and persistence.…”
Section: Case Study Atmospheric Blockingmentioning
confidence: 99%